2019
DOI: 10.1080/13816810.2019.1582069
|View full text |Cite
|
Sign up to set email alerts
|

A high prevalence of biallelicRPE65mutations in Costa Rican children with Leber congenital amaurosis and early-onset retinal dystrophy

Abstract: Background: Leber Congenital Amaurosis (LCA) and Early Onset Retinal Dystrophy (EORD), are primary causes of inherited childhood blindness. Both are autosomal recessive diseases, with more than 25 genes explaining approximately ~70% of cases. However, the genetic cause for many cases remains unclear. Sequencing studies from genetically isolated populations with increased prevalence of a disorder has proven useful for rare variant studies, making Costa Rica an ideal place to study LCA/EORD genetics. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A total of 212 pathogenic variants in RPE65 have been reported to date (HGMD, [17]), of which the majority are missense (54.71%), followed by nonsense-frameshift (32.54%) and splice site variants (12%). A similar frequency of the type of mutation was observed in our cohort (57%, 28% and 11%, respectively); thus, our cohort is representative of the first described in LCA patients from India [15] and Central America [45], being related to more severe phenotypes. Interestingly, p.(Ile98Hisfs*26) seems to represent a founder mutation in our cohort with all the carriers families sharing a common haplotype.…”
Section: Genotype-phenotype Correlationsupporting
confidence: 85%
See 2 more Smart Citations
“…A total of 212 pathogenic variants in RPE65 have been reported to date (HGMD, [17]), of which the majority are missense (54.71%), followed by nonsense-frameshift (32.54%) and splice site variants (12%). A similar frequency of the type of mutation was observed in our cohort (57%, 28% and 11%, respectively); thus, our cohort is representative of the first described in LCA patients from India [15] and Central America [45], being related to more severe phenotypes. Interestingly, p.(Ile98Hisfs*26) seems to represent a founder mutation in our cohort with all the carriers families sharing a common haplotype.…”
Section: Genotype-phenotype Correlationsupporting
confidence: 85%
“…By contrast, the most common alleles found in our cohort were p.(Ile98Hisfs*26, p.(Pro111Ser) and p.(Gly187Glu). The p.(Ile98Hisfs*26) variant was first described in LCA patients from India [15] and Central America [45], being related to more severe phenotypes. Interestingly, p.(Ile98Hisfs*26) seems to represent a founder mutation in our cohort with all the carriers families sharing a common haplotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, EYS gene variants were found to be causative in 51% of a RP cohort from Japan [ 36 ]. This discovery is not unique, as several other parallel studies have revealed similar founder mutations in their target populations, for example, Belgium, RAX2 [ 37 ]; Costa Rica, RPE65 [ 38 ]; Finland, CERKL [ 39 ]; Japan, EYS [ 36 ]; Spain, RP1 [ 40 ] and ABCA4 [ 41 ]; Jewish community in Caucasia, PDE6B [ 42 ]; Pakistan, ABCA4 and NMNAT1 [ 43 ]; Guyana, BBS9 [ 44 ]; and Faroe Islands, MERTK [ 45 ]. The enrichment of these variants, several of which are large structural variants, emphasises the value of population-specific TS panels to target and detect mutations and mutational breakpoints that may be missed by commercial generic gene panel sequencing or even WES.…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 66%
“…2,6,75 Over 100 mutations are associated with the pathogenesis of arLCA, 2,6,75-78 RP. 6,[75][76][77] adult onset vitelliform macular dystrophy 79 and CRD. 80 Although it may produce both adRP and arRP, it is mostly associated with arRP.…”
Section: Rpe65 Genementioning
confidence: 99%